3D laparoscopic prostatectomy: results of multicentre study . (4th May 2022) - Haapiainen, Henry; Kaipia, Antti; Murtola, Teemu; Seikkula, Heikki; Seppänen, Marjo; Jämsä, Pyry; Raitanen, Mika
Abstract: Introduction: Three-dimensional laparoscopic prostatectomy (3D LRP) is a potentially cost-effective option for robot-assisted laparoscopic prostatectomy (RALP). Results for two-dimensional LRP and RALP are well documented; however, little has been published on the outcomes of 3D LRP. Our objective was to report the perioperative and short-term results of 3D LRP in a multicentre study. Materials and methods: In total, 496 unselected men with prostate cancer underwent 3D LRP by three surgeons between December 2013 and December 2018. Median age was 64 (43–76) years. Median prostate-specific antigen (PSA) was 7.9 (0.7–148) ng/ml. Preoperative and perioperative data and complications according to the Clavien–Dindo classification were collected. PSA and continence results were reported at 3 and 12 months postoperatively. Data were analysed with IBM SPSS statistics (25). Results: Pathological Gleason score was 6 in 29%, 7 in 55.4%, 8 in 9.1%, 9 in 5.2% and 10 in 1.2% of patients. Pathological tumour classification was T2c in 59.5%, T3a in 19.5% and T3b in 10.9% of cases. Positive surgical margins occurred in 27.2%. Lymphadenectomy was performed in 36.3%, with positive lymph nodes in 11.8%. Median operative time was 137 (78–334) min and median blood loss 200 (10–1100) ml. Clavien–Dindo IIIa and IIIb complications occurred in 6.9% and 1.6%, respectively. At 3 and 12 months postoperatively, 90.2% and 91.4% of patients, respectively, had PSA <0.2 ng/ml, while 77.1% and 87.7% of patients were completely dry or using a maximum of one pad daily. Conclusions: 3D LRP shows promising results, comparable to similar studies published on RALP.